Pengaruh Kebersyukuran dan Dukungan Keluarga terhadap Resiliensi Ibu yang Memiliki Anak Tunarungu - Nida Salsabila; Itsna Nurrahma Mildaeni; Ugung Dwi Ario Wibowo; Nia Anggri Noveni (PSIMPHONI, 2024)
Raising children with special needs is a challenging process that requires understanding, support, and adjustments from parents, especially mothers. Therefore, resilience is a crucial factor that enables mothers of children with hearing impairments to remain strong, endure difficulties, and recover from adversity. This study aims to analyze the influence of gratitude and family support on the resilience of mothers with children with hearing impairments at SLB B Yakut Purwokerto. This research employs a quantitative method, involving 112 mothers as participants, with data analyzed using multiple linear regression through SPSS for Windows version 26.00. The results indicate that gratitude has a significant effect on resilience, with an F-value of 50.713 and a significance value (p) = 0.000 (p < 0.050), contributing 31.6%. Family support also significantly affects resilience, with an F-value of 38.057 and a significance value (p) = 0.000 (p < 0.050), contributing 25.7%. Simultaneously, gratitude and family support contribute 39% to maternal resilience, with an F-value of 34.874 and a significance value (p) = 0.000 (p < 0.050). Based on these findings, it is recommended that mothers of children with hearing impairments develop gratitude as a strategy to enhance their resilience. Additionally, families are encouraged to provide more intensive support, both emotionally, instrumentally, and socially, to strengthen the mothers’ psychological endurance. Educational institutions and communities can also play a role in offering mentoring programs and psychosocial support to assist mothers in facing the challenges of raising children with hearing impairments.